Risk Factors of Pneumocystis Pneumonia in Solid Organ Recipients in the Era of the Common Use of Posttransplantation Prophylaxis. Issue 1 (12th December 2014) - Iriart, X.; Challan Belval, T.; Fillaux, J.; Esposito, L.; Lavergne, R.‐A.; Cardeau‐Desangles, I.; Roques, O.; Del Bello, A.; Cointault, O.; Lavayssière, L.; Chauvin, P.; Menard, S.; et al.
<x xml:space="preserve">Abstract</x> Pneumocystis pneumonia (PCP) in solid organ transplant (SOT) recipients becomes rare in the immediate posttransplantation period thanks to generalized prophylaxis. We aimed to identify the predictive factors for PCP in the era of universal prophylaxis and to propose a strategy for preventing PCP beyond the first year after transplantation. In a retrospective case–control study, 33 SOT cases with PCP diagnosed between 2004 and 2010 were matched with two controls each to identify risk factors for PCP by uni‐ and multivariate analysis. All the patients benefited from 6 months of posttransplantation trimethoprim–sulfamethoxazole prophylaxis. Most PCP in SOT patients occurred during the second year posttransplantation (33%). By univariate analysis, age, nonuse of tacrolimus, total and CD4 lymphocyte counts, gamma‐globulin concentration and cytomegalovirus (CMV) infection appeared to be PCP risk factors. In the final multivariate analysis, age (adjusted odds ratio [OR] 3.7, 95% confidence interval [CI]: 1.3–10.4), CMV infection (OR: 5.2, 95% CI: 1.8–14.7) and total lymphocyte count (OR: 3.9, 95% CI: 1.4–10.7) were found to be independently associated with PCP. The second year posttransplantation appeared to be the new period of highest risk of PCP. Age, CMV viremia and lymphocytes were the most pertinent predictive criteria to evaluate the risk of PCP in clinical practice.